A new approach for short-spacing correction of radio interferometric datasets - Faridani, Shahram; Bigiel, Frank; Flöer, L.; Kerp, J.; Stanimirović, S. (Astronomische Nachrichten, 2018)
The short-spacing problem describes the inherent inability of radio-interferometric arrays to measure the integrated flux and structure of diffuse emission associated with extended sources. New interferometric arrays, such as Square Kilometer Array (SKA), require solutions to efficiently combine interferometer and single-dish data. We present a new and open-source approach for merging single-dish and cleaned interferometric datasets, requiring a minimum of data manipulation while offering a rigid flux determination and full high-angular resolution. Our approach combines single-dish and cleaned interferometric data in the image domain. This approach is tested for both galactic and extragalactic Hi datasets. Furthermore, a quantitative comparison of our results with commonly used methods is provided. Additionally, for the interferometric datasets of NGC 4214 and NGC 5055, we study the impact of different imaging parameters as well as their influence on the combination for NGC 4214. The approach does not require raw data (visibilities) or any additional special information, such as antenna patterns. This is advantageous, especially in the light of upcoming radio surveys with heterogeneous antenna designs.
Gesehen am 22.04.2020